The relationship between Alzheimer’s disease and intestinal microflora structure and inflammatory factors - Wang, Su-shan; Li, Xiao-hui; Liu, Ping; Li, Jing; Liu, Li (Frontiers in Aging Neuroscience, 2022)
To analyze the structural characteristics of intestinal microflora and changes of serum inflammatory factors of the Alzheimer's disease, and to explore the relationship between them and dementia, we selected 30 patients in the AD group and 30 patients in the normal group, and collected stool samples to analyze the intestinal flora structure characteristics of the two groups of patients, and statistically analyzed the inflammatory cytokines TNF-α, IL-1β, IL-6, IL-8 by ELISA from the venous blood of the two groups. The results show that the dominant bacteroides in the two groups are Bacteroides, Firmicutes, Proteobacteria and actinobacteria. The abundance of Bacteroides, Firmicutes and Proteobacteria in the AD group shows a statistical difference. At the genus level, the abundance of anti-inflammatory bacteria such as Lactobacillus, Bifidobacterium and Rumen bacteria drops in AD group, while the abundance of pro-inflammatory bacteria such as Escherichia and Enterococcus raises. Statistical analysis of inflammatory cytokines in the two groups suggests that TNF-α and IL-6 levels significantly increase in the AD group, with statistical differences. Therefore, it is speculated that the increased abundance of pro-inflammatory bacteria in intestinal flora may lead to or aggravate neuroinflammation through the release of inflammatory factors, thus further leading to the occurrence and development of AD.